Hipoalbuminemia como factor de riesgo de mortalidad en adultos mayores con NAC Hospital del Hospital Víctor Lazarte Echegaray de Trujillo en el periodo enero 2021 a junio 2022 - Sachun Plasencia, Manuel Antonio (2022)
The objective was to determine whether hypoalbuminemia is a risk factor for mortality in older adults with community-acquired pneumonia. A study of cases and controls from hospitalized patients in the Department of Medicine Hospital Victor LAzarte Echegaray of Trujillo of January 1, 2021 until June 31, 2022 was performed. Following randomization, 41 patients were included as cases and 83 patients as controls.